2021
DOI: 10.1177/0022146520979645
|View full text |Cite
|
Sign up to set email alerts
|

Colorism and Physical Health: Evidence from a National Survey

Abstract: This study uses nationally representative data to extend a steadily growing body of research on the health consequences of skin color by comparatively examining the consequences of perceived ingroup and outgroup skin color discrimination (perceived colorism) for physical health among African Americans. Using a comprehensive set of measures of physical health, I find that perceived ingroup colorism is significantly associated with worse physical health outcomes among African Americans. Notably, the magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…The social ecological framework integrates influences from the individual, interpersonal, community and structural levels. It also emphasizes that these levels interact with one another, and that interaction of factors is as important as each individual level [7]. Building on the use of the social ecological model, the conceptual framework also incorporates the life course framework.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The social ecological framework integrates influences from the individual, interpersonal, community and structural levels. It also emphasizes that these levels interact with one another, and that interaction of factors is as important as each individual level [7]. Building on the use of the social ecological model, the conceptual framework also incorporates the life course framework.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Some of the negative coping strategies can physically or mentally affect the body leading to health issues such as depression or anxiety for both men and women (e.g., Borrell et al, 2006;Pascoe & Richman, 2009). Yet the effects of colorism in healthcare settings are largely unexplored in psychological literature, even though there is some evidence that dark skin is associated with poorer outcomes in mental health (e.g., Oh et al, 2021;Williams & Williams-Morris, 2000) and physical health (e.g., Keyes et al, 2020;Landor & McNeil Smith, 2019;Monk, 2021;Sweet et al, 2007). Therefore, this study also addressed the effects of colorism in various settings, including healthcare.…”
Section: Colorismmentioning
confidence: 99%
“…The Boston Puerto Rican Health Study included both men and women, also the proportion of AFR ancestry in people of Puerto Rican heritage is higher than that of the other Hispanic heritage groups included in the WHI so the contribution of the AFR ancestry to the development of CVD could differ within Hispanic heritage-groups 24 . Regarding the effect of AFR ancestry over the risk of CVD, it has been previously reported that a substantial proportion of the effect of AFR ancestry over the risk of disease can be attributed to socioeconomic and cultural factors like barriers to access to health care, racism, and discrimination, among others 14,25 . A study that involved 87 adults from Puerto Rico evaluated if African ancestry or a social classification of skin pigmentation (color: blanco or white, the intermediate category trigueño, and negro or black) better predicts blood pressure.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%